Respiratory Support After Extubation in Children With Pediatric ARDS - Wong, Judith Ju Ming; Tan, Herng Lee; Sultana, Rehena; Ma, Yi-Jyun; Aguilan, Apollo Bugarin; Goh, Chen Yun; Lee, Wen Cong; Kumar, Pavanish; Lee, Jan Hau (Respiratory care, 2024)
Postextubation respiratory support in pediatric ARDS may be used to support the recovering respiratory system and promote timely, successful liberation from mechanical ventilation. This study's aims were to (1) describe the use of postextubation respiratory support in pediatric ARDS from the time of extubation to hospital discharge, (2) identify potential risk factors for postextubation respiratory support, and (3) provide preliminary data for future larger studies. This pilot single-center prospective cohort study recruited subjects with pediatric ARDS. Subjects' respiratory status up to hospital discharge, the use of postextubation respiratory support, and how it changed over time were recorded. Analysis was performed comparing subjects who received postextubation respiratory support versus those who did not and compared its use among pediatric ARDS severity categories. Multivariable logistic regression was used to determine variables associated with the use of postextubation respiratory support and included oxygenation index (OI), ventilator duration, and weight. Seventy-three subjects with pediatric ARDS, with median age and OI of 4 (0.6-10.5) y and 7.3 (4.9-12.7), respectively, were analyzed. Postextubation respiratory support was provided to 54/73 (74%) subjects: 28/45 (62.2%), 19/21 (90.5%), and 7/7 (100%) for mild, moderate, and severe pediatric ARDS, respectively, ( = .01). OI and mechanical ventilation duration were higher in subjects who received postextubation respiratory support (8.7 [5.4-14] vs 4.6 [3.7-7], < .001 and 10 [7-17] d vs 4 [2-7] d, < .001) compared to those who did not. At hospital discharge, 12/67 (18.2%) survivors received home respiratory support (6 subjects died prior to hospital discharge). In the multivariable model, ventilator duration (adjusted odds ratio 1.3 [95% CI 1.0-1.7], = .050) and weight (adjusted odds ratio 0.95 [95% CI 0.91-0.99], = .02) were associated with the use of postextubation respiratory support. The majority of intubated subjects with pediatric ARDS received respiratory support postextubation, and a substantial proportion continued to require it up to hospital discharge.